Die deutsch-griechischen Beziehungen im Bereich der Wissenschaft/Rede des Präsidenten des Europäischen Gerichtshofs Vassilios Skouris zur Eröffnung der ,,Conference on Scientific Cooperation between Greece and Germany an der Universität Hamburg vom 5. bis 7. Februar 2015" - Nicolaysen, Rainer (Hamburger Universitätsreden Neue Folge, 2016)
From February 5th till 7th, 2015, the "Conference on Scientific Cooperation between Greece and Germany" took place at the University of Hamburg. About 100 scientists from Greece and Germany invited by the President of the University, Dieter Lenzen, took part in the project, discussing the current crisis in Greece which also dramatically affects scholarship there and whose effects are now a fundamental threat to the functioning of the Greek university system. This volume documents the German version of the English-language welcome speech of the President of the University in which he emphasizes the urgency of joint action as well as the opening speech by the President of the European Court of Justice Vassilios Skouris in German. Skouris describes the specifics of the scientific relations between Greece and Germany in both historical and contemporary terms.